How JustAnswer Works:
  • Ask an Expert
    Experts are full of valuable knowledge and are ready to help with any question. Credentials confirmed by a Fortune 500 verification firm.
  • Get a Professional Answer
    Via email, text message, or notification as you wait on our site. Ask follow up questions if you need to.
  • Go back-and-forth until satisfied
    Rate the answer you receive.
Ask Sandhya_sharma Your Own Question
Sandhya_sharma, Master's Degree
Category: Pre-Calculus
Satisfied Customers: 10699
Experience:  I hold M.Sc and M.Phil degrees in math and have several years of teaching experience.
Type Your Pre-Calculus Question Here...
Sandhya_sharma is online now

T(s(x))) t(x) = 2x-6 s(x) = 1/2x+3 So t(1/2x+3) 2(1/2x+3)-6

This answer was rated:

t(s(x)))t(x) = 2x-6
s(x) = 1/2x+3So t(1/2x+3)2(1/2x+3)-6= 1x+6-6= 1x?


= t((1/2)x + 3)

replace x by (1/2)x + 3 in definition of t(x)

= 2((1/2)x + 3) - 6

open parenthesis

= x + 6 - 6

= x

I hope it will help you.


Sandhya_sharma and other Pre-Calculus Specialists are ready to help you
Customer: replied 6 days ago.
Well suppose 1x and x are the same thing so looks like I'm somewhat understanding it now, haha. Thank you.

yes, 1x and x are the same..

If you get 1x then just write it x..

I hope it will help.


sorry, I missed your request.

Please request me if you still need help.